3D spatial distribution of old landfills and groundwater pollution from electrical resistivity tomography with fuzzy set theory. Issue 2 (4th March 2022) - Wang, Xian-Xiang; Chang, Yong-bang; Deng, Ju-Zhi; Chen, Jia-song
Abstract : Landfill leakage is a concerning source of soil and groundwater pollution. Geophysical methods have been widely used in the exploration of landfill structure and leakage. However, a disadvantage of this method is its inability to delineate the landfill and the leakage area finely. By employing the membership function of fuzzy mathematics, this paper presents a quantitative index of groundwater pollution, which can clearly show the groundwater pollution status of landfills. In this manuscript, a specific landfill in Beijing was used as an example. A total of 11 electrical resistivity tomography (ERT) profiles were gathered to obtain the geoelectrical structure of the landfill. Then, we convert ERT inversion results into a quantitative index for groundwater pollution using the fuzzy set theory. Some drill samples, collected from landfill boreholes, are analysed for ammonia-nitrogen concentration to determine the parameters of the membership function. Through the comprehensive analysis of drilling, sample testing, and ERT results, we have established an indicator system that can be genuinely applied in the field for the identification and determination of leachate contaminated soil. We obtained the 3D spatial distribution of groundwater pollution, which can provide accurate and reliable data for treating landfill leakage.